Myoklonien als Bewegungsstörung - Meinck, Hans-Michael (Der Nervenarzt, 2017)
Myoclonus is often a diagnostic and therapeutic challenge due to its broad phenomenological variability and limited therapeutic options. This article gives a short survey and characterizes in detail two common types of myoclonus, cortical myoclonus and reticular reflex myoclonus. Clinical testing and electrophysiological investigations provide relevant local diagnostic indications for the generating structure(s). Such indications would influence not only the strategies of neuroimaging and laboratory investigations aimed at clarifying the underlying cause but also the selection of drugs to suppress myoclonus.